Design and Implementation of the Components of the Symmetric Cryptographic Algorithm - Ci, Yunfei; Shi, Guozhen; Yang, Feng; Diao, Jiawen; Liu, Cuijie; Mao, Weihua (2017 IEEE Second International Conference on Data Science in Cyberspace (DSC), 2017)
Cryptographic technology is the basic and core technology to guarantee network and information security. It is imperative to standardize cryptographic algorithms. Cryptographic algorithm test is the most important research content of cryptographic normalization. Symmetric cryptographic algorithms are the most widely studied and applied. So it has the practical value to normalize the symmetric cryptographic algorithm. Symmetric cryptographic algorithm test tool is the most important design of the test method components. The test method components of this paper mainly include 20 kinds of random test methods. In order to shorten the test time and improve the efficiency of the test, the random test method of the component is also realized by multi-thread programming. The experiment verifies that the test tool can obtain the correct test result and can improve the flexibility of the test method.